ICT and agricultural sector performance: empirical evidence from sub-Saharan Africa - Lukman O. Oyelami; Nurudeen Afolabi Sofoluwe; Omowumi Monisola Ajeigbe (Future Business Journal, 2022)
Abstract ICT infrastructure is considered crucial to performance and overall development of many sectors in sub-Saharan Africa (SSA). Yet, there exists insufficient evidence on the effect of ICT on agriculture real output and export performance in the African continent. This study investigates the effect of ICT infrastructure on agriculture sector performances in SSA using panel autoregressive distributed lag (ARDL) approach. Panel data were collected over the period of twenty-three (23) years (1995–2017) in 39 SSA countries. Two models were specified using agricultural value addition and agriculture products as a percentage of total merchandise export as dependent variables. Key independent variables include mobile-cellular telephone subscription and individual using the internet. The study also introduced important control variables such as livestock production index and crop production index. The results from the estimation provide substantial evidence to show that ICT infrastructure has positive externality on agricultural sector performances in the long run. However, there is no evidence to maintain this position in the short run. The study, therefore, recommends that there should be a cautious approach to increasing investment in ICT infrastructure. Provision of in ICT infrastructure alone may not automatically improve agricultural output. Thus, there is a need for extension services to propagate and educate farmers on the importance of continuous adoption of ICT infrastructure for agricultural practices in SSA.